The road warrior [videorecording (DVD)] - Miller, George, 1945 March 3-; Gibson, Mel; Spence, Bruce; Preston, Michael, 1938- (Warner Home Video, 1997)
Story is set in the post-nuclear outback of Australia where a battle is raged by a tiny band of civilized survivors and a group of barbarians over a precious cache of gasoline.